Father Involvement in Islamic Parenting: The Role of Paternal Spiritual Leadership in Child Emotional Security - Eva Nurajizah (Islamic Counseling and Parenting Journal, 2025)
and developmental outcomes, yet limited research has examined its spiritual dimension within Islamic parenting. This study investigates the role of paternal spiritual leadership in shaping children’s emotional security, focusing on how fathers’ religious modeling, daily routines, and emotional communication influence children’s psychological well-being. Using a qualitative phenomenological design, data were collected through semi-structured interviews, non-participant observations, and documentation from Muslim families characterized by varying levels of paternal engagement. Thematic analysis revealed four core dimensions of father involvement: spiritual modeling, emotional communication, religious routines, and father–child bonding. Results indicate that consistent paternal spiritual leadership is strongly associated with high emotional security, reflected in children’s trust, emotional expression, identity clarity, and stress regulation. In contrast, inconsistent or minimal father involvement contributed to moderate or low emotional security, often characterized by anxiety or identity instability. The study concludes that spiritual leadership functions as both an emotional anchor and moral compass in Islamic parenting, reinforcing children’s resilience and socio-emotional stability. These findings highlight the need for father-focused interventions that integrate emotional responsiveness and spiritual guidance to strengthen family well-being.